Embryonic and larval development of Eugerres mexicanus (Perciformes: Gerreidae) in Tenosique: Tabasco, Mexico - Raúl E Hernández; Martha A. Perera; Alfonso Castillo; Emiliano Luna H; José A. de la Cruz; Luis M. Gómez; José Valdez Zenil (Revista de Biología Tropical, 2012)
Most studies on Eugerres mexicanus mainly consider biogeographic and systematic aspects and rarely address reproductive characteristics, which are useful for fishery population management plans. This study aimed at evaluating the ontogeny of E. mexicanus, based on 30 embryos and 30 larvae sampled by induced spawning of breeders, taken in February 2009 from the Usumacinta River in Tenosique, Tabasco, Mexico. All descriptions of the embryonic development were based on morphometric and meristic data and followed standard methods. Eggs, recovered at the gastrula stage, had an average diameter of 1.17mm (SD=0.08). The bud stage appeared during the first three hours of development, in which the posterior side was adhered to the vitellus; Kupffer´s vesicle was visible. Yolk-sac larvae hatched 18 hours after fertilization, exhibiting a light brown color and an average total length of 2.94mm (SD=0.70); the preflexion stage was reached eight days after hatching, with a total average length of 4.67mm (SD=0.50) and a total notochord length of 4.45mm (SD=0.50). The flexion stage was reached on the 16th day, with an average total length of 6.66mm (SD=1.53), while postflexion was reached on the 24th day, with 10.33mm (SD=1.45). The pre-juvenile stage was reached on the 33rd day, with a total length of 14.30mm (SD=0.93), showing IX spines and 10 rays and III spines and eight rays in the dorsal and anal fins, respectively. The juvenile stage was reached by the 45th day, with an average length of 28.16mm (SD=1.93) and average weight of 4.75g (SD=1.49). Prejuveniles showed an initial pigmentation with dark colored dots in the superior and inferior jaw and dispersed on the head, while juveniles presented the same pigmentation pattern, decreasing towards the margin of the caudal peduncle. In conclusion, the embryonic developmental stages of E. mexicanus were typical for the Gerreidae group. However, their morphometric characters were slightly different since the diameter and size of the drop of oil were bigger than those reported for marine species. In addition, regarding pigmentation, the yolk-sac larvae of E. mexicanus were olive and yellow on the margin of the notochord, which differs from those reported for other species. This is the first recorded report on the reproductive biology and early life development of this species. La ontogenia se basó en 30 embriones y 30 larvas, obtenidos mediante la inducción del desove de reproductores provenientes de la ribera del río Usumacinta en Tenosique, Tabasco, México, recolectados en febrero de 2009. La descripción se fundamentó en el registro morfométrico y merístico. Los huevos fueron recuperados en estado de gástrula y presentaron un diámetro de promedio de 1.17mm (SD=0.08). Durante las primeras tres horas de desarrollo embrionario, se presentó la etapa de capullo, en la que se observó la región caudal adherida al vitelo, apreciándose la vesícula de Kupffer. Las larvas con saco eclosionaron a las 18 horas pos-fertilización, fueron de color marrón claro con un promedio de 2.94mm; (SD=0.70) de longitud total y alcanzaron la preflexión a los ocho días post-eclosión con una longitud total promedio de 4.67mm; (SD=0.50) y una longitud total del notocordio de 4.45; (SD=0.50). A los 16 días de la eclosión alcanzaron la flexión, con un promedio de 6.66mm; (SD=1.53) de longitud total. La postflexión se presentó a los 24 días con 10.33mm; (SD=1.45). Al llegar a los 33 días, se presentó la fase prejuvenil y llegaron a medir 14.30; (SD=0.93) de longitud total, presentando IX espinas y 10 radios en la aleta dorsal y III y ocho en la aleta anal. Los juveniles midieron 28.16; (SD=1.93) de longitud a los 45 días, con un peso promedio de 4.75g; (SD=1.49). Los prejuveniles presentaron una pigmentación inicial en la mandíbula superior e inferior con tintes oscuros en forma de puntos y de manera dispersa sobre la cabeza. En los juveniles se observó el mismo patrón de pigmentación, disminuyendo hacia el margen del pedúnculo caudal. Las características descriptivas de la etapa de desarrollo embrionario de E. mexicanus son típicas del período de desarrollo de los peces de la familia Gerreidae, en particular en el caso de las especies E. brasilianus y E. lineatus que habitan en ambientes marinos. Sin embargo, sus caracteres morfométricos son diferentes con respecto al diámetro y el tamaño de los huevos y de la gota de aceite, ya que en E. mexicanus son más grandes que los de las especies marinas y son similares a los de los peces de agua dulce. Con respecto a la pigmentación, la larva con saco de E. mexicanus presenta un olor olivo y amarillo sobre el margen del notocordio, lo cual difiere a lo reportado para E. lineatus,ya que en esta muestra un grupo de melanóforos entre los miomeros nueve al 13 como principal característica, y para Diapturus peruvianus por presentar tres manchas en el margen dorsal de los intestinos desde la inserción de la aleta pectoral hasta el ano. Los resultados de este estudio son los primeros registrados para esta especie y han generado información sobre aspectos de su biología reproductiva y el desarrollo de la vida temprana.